Estimating accrual-based models in Poland: the time series data approach and the cross-sectional data approach - Comporek, Michał (Publishing House of Wroclaw University of Economics and Business, 2021)
The analysis of accruals can be considered as an important tool for examining the level and the patterns of earnings management phenomenon in an enterprise. This paper compares the empirical features of different accrual-based models within industrial public companies listed on the Warsaw Stock Exchange in the period 2002-2017. The conducted research is focused not only on examining the empirical validity of the original Jones model, the modified Jones model and the ROA-matched Jones model. It also submits the alternative regression model used for the detection of earnings management practices, taking into account the following independent variables: operational expenses as a proxy for the current components of non- discretionary accruals, as well as intangible assets as a proxy for the noncurrent components of non-discretionary accruals. Then, the authorexamined the probability of occurrence of small increases in net income or big bath charges in companies reporting specific values of discretionary accruals. The conclusions drawn in this paper are part of practical research concerning the use of informational and decision-making features of accruals analysis in the Polish post-transitional capital market, acting simultaneously as a prerequisite for further research in this field
Argumenta Oeconomica, 2021, Nr 1 (46), s. 205-237